A Comprehensive Review of Peru’s Energy Scenario: Advancing Energy Access, Sustainability, and Policy Implications - Colina-Calvo, Aaron Omar (2024)
Peru is in the race to eliminate poverty, inequality and environmental pollution according to the Sustainable Development Goals (SDGs) by 2030; however, the country faces significant challenges in the energy sector, with limited access to electricity and a heavy dependence on imported wood and fuels. This study explores the Peruvian energy context, focusing on an integrative model based on policies, emissions, challenges and opportunities to ensure the availability of resources and a sustainable framework for development through the evaluation of indicators and impacts within the energy sector. Our findings show that energy consumption in Peru depends on diesel, natural gas, and wood. Despite the country's efforts to advance renewable sources of energy and their potential, their contribution is approximately 5%. In this regard, sustainability policies towards 2030 have been adopted by promoting various initiatives, such as installing off-grid photovoltaic panels, BonoGas tickets or energy efficiency measures. However, the lack of political, economic, social and institutional support for emerging technologies slows down progress according to the proposed model.